2013
DOI: 10.3319/tao.2012.10.17.01(sec)
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Comparison of Zonal Mean and Tidal Signatures in FORMOSAT-3/COSMIC and Ground-Based GPS TECs

Abstract: Atmospheric tidal components in the ionosphere can reflect either the in-situ generated quiet-time variation in the ionosphere, or vertically propagating tidal components generated through coupling to lower or middle atmosphere phenomena. Frequency-wavenumber tidal decomposition is a valuable tool for isolating the primary tidal components that drive the dynamics of the middle and upper atmosphere, allowing temporal and spatial variability to be quantified in a systematic manner, provided sufficient local time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…In Figures , , and , we can find either a wave 1 with single maximum and minimum or a wave 2 with two maxima and minima. This is not entirely unexpected as past studies have found that the wave‐3 and wave‐4 components in GIM TECs tend to be underestimated compared to those retrieved from satellite observations [ Jee et al ., ; Chang et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…In Figures , , and , we can find either a wave 1 with single maximum and minimum or a wave 2 with two maxima and minima. This is not entirely unexpected as past studies have found that the wave‐3 and wave‐4 components in GIM TECs tend to be underestimated compared to those retrieved from satellite observations [ Jee et al ., ; Chang et al ., ].…”
Section: Discussionmentioning
confidence: 99%